PENGARUH METODE PEMBELAJARAN TUTOR SEBAYA (PEER TEACHING) TERHADAP HASIL BELAJAR SISWA SEKOLAH MENENGAH PERTAMA - Wahidah, Nur; Nasihin, Durrotun; Rofiq, M. Nafiur (UAS PRESS, 2025)
Your The use of learning methods not only makes it easier to deliver material but can also help improve learning outcomes, build joy and comfort in learning. There are various methods that can be used by teachers, including the peer tutoring method. Peer tutoring is a learning method based on active learning, which is a teaching and learning activity in class that gives students the opportunity to teach and share knowledge and skills with other students to help their friends who are having difficulty learning so that their friends can understand the material well. good This research succeeded in concluding that the results of the posttest in the experimental class and control class using the independent sample ttest obtained a sig (2-tailed) value of 0.000. This value shows that the Sig (2-tailed) value is <0.05 so that the Alternative Hypothesis (Ha ) is accepted and the Null Hypothesis (H0) is rejected. Then it can be concluded that there is an influence of the peer tutoring learning method on student learning outcomes in Islamic religious education lessons in junior high schools.